(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research aimed to identify the attitudes of faculty members at Preparation Training Institute in Tartous toward the use of Artificial Intelligence (AI) applications in education. The descriptive-analytical method was used, and to achieve the research objectives, the researcher designed a scale consisting of (54) items. Which was applied to a sample of (49) male and female teachers from the faculty of teacher training institutes in Tartous. The research results showed that Opinions and the attitudes of faculty members in the Teacher Training Institutes, departments in Tartous toward the use of Artificial Intelligence applications in education were positive, , with an arithmetic mean of (3.71) and a relative weight of (70.6%). The results also indicated statistically significant differences in the attitudes of statistically significant differences in attitudes of the research sample of faculty members in the teachers training institutes, attributable to the specialization variable, in favor of the Fine Arts Education Department. However, there were no statistically significant differences in the attitudes of the research sample of faculty members according to the number of years of experience at the level of the total score of the scale, . In light of the findings reached by the research, the researcher proposed designing training programs aimed at qualifying educational staff to use artificial intelligence applications, as well as providing the necessary infrastructure to support AI applications in education